Utilization status of Safe Motherhood Program: a study from Jumla district, Nepal - Shahi, Shubhadra; Neupane, Dinesh Raj; Ranabhat, Kamal; Wagle, Subash; Rajbanshi, Manish; Adhikari, Anita; Niroula, Sandhya; Kafle, Hari Prasad (International Journal Of Community Medicine And Public Health, 2024)
Background: Safe Motherhood Program is a national priority programme that aims to reduce maternal and neonatal mortality and morbidity through demand and supply side incentives and free delivery care. The study investigates Safe Motherhood Program’s utilization, changes post-implementation, and associated factors in Jumla district to enhance maternal health care access and reduce preventable maternal deaths. Methods: A community based cross sectional study using quantitative approach was conducted where the women of reproductive age group having at least one child of 3-15 months of age were interviewed using the semi structured interview schedule (n=228). Chi square test was used to show the association with independent and depended variables. All the test was carried out at the statistically significant of p value <0.05. Results: The study revealed significant associations between utilization of maternal health care services and various factors: respondent’s education level (p=0.034, OR=1.834, CI=1.043-3.223), husband’s education level (p=0.007, OR=2.300, CI=1.252-4.228), respondent’s employment status (p=0.003, OR=7.155, CI=1.650-31.029), husband’s employment status (p=0.001, OR=2.778, CI=1.526-5.055), monthly income (OR=5.556, CI=2.005-15.393), and involvement in social groups (p=0.009, OR=2.312, CI=1.217-4.390). Conclusions: Despite strong awareness of delivery incentives, the program success was restricted by poor knowledge of checkup incentives. The study identified the sociodemographic factors influencing the appropriate use of Jumla’s Safe Motherhood Program scheme. Pregnancy was highly registered, however less than two thirds of women had the necessary number of examinations performed. Institutional deliveries increased but there was disparity during the service delivery.